Cross-Species Application of Illumina iScan Microarrays for Cost-Effective, High-Throughput SNP Discovery - Fountain, Emily D.; Zhou, Li-Chen; Karklus, Alyssa; Liu, Qun-Xiu; Meyers, James; Fontanilla, Ian K. C.; Rafael, Emmanuel Francisco; Yu, Jian-Yi; Zhang, Qiong; Zhu, Xiang-Lei; Pei, En-Le; Yuan, Yao-Hua; et al. (Frontiers in Ecology and Evolution, 2021)
Microarrays can be a cost-effective alternative to high-throughput sequencing for discovering novel single nucleotide polymorphisms (SNPs). Illumina’s iScan platform dominates the market, but their commercial microarray products are designed for model organisms. Further, the platform outputs data in a proprietary format. This cannot be easily converted to human-readable genotypes or be merged with pre-existing data. To address this, we present and validate a novel pipeline to facilitate data analysis from cross-species application of Illumina microarrays. This facilitates the generation of a compatible VCF from iScan data and the merging of this with a second VCF comprising genotypes derived from other samples and sources. Our pipeline includes a custom script, iScanVCFMerge (presented as a Python package), which we validate using iScan data from three great ape genera. We conclude that cross-species application of microarrays can be a rapid, cost-effective approach for SNP discovery in non-model organisms. Our pipeline surmounts the common challenges of integrating iScan genotypes with pre-existing data.